Glomerular Filtration Rate Measured by (51)Cr-EDTA Clearance: Evaluation of Captopril-Induced Changes in Hypertensive Patients with and without Renal Artery Stenosis - Chaves, Anna Alice Rolim (Hospital das Clínicas da Faculdade de Medicina da Universidade de São Paulo, 2010)
INTRODUCTION: Renal artery stenosis can lead to renovascular hypertension; however, the detection of stenosis alone does not guarantee the presence of renovascular hypertension. Renovascular hypertension depends on activation of the renin-angiotensin system, which can be detected by functional tests such as captopril renal scintigraphy. A method that allows direct measurement of the baseline and post-captopril glomerular filtration rate using chromium-51 labeled ethylenediamine tetraacetic acid ((51)Cr-EDTA) could add valuable information to the investigation of hypertensive patients with renal artery stenosis. The purposes of this study were to create a protocol to measure the baseline and post-captopril glomerular filtration rate using (51)Cr-EDTA, and to verify whether changes in the glomerular filtration rate permit differentiation between hypertensive patients with and without renal artery stenosis. METHODS: This prospective study included 41 consecutive patients with poorly controlled severe hypertension. All patients had undergone a radiological investigation of renal artery stenosis within the month prior to their inclusion. The patients were divided into two groups: patients with (n=21) and without renal artery stenosis, (n=20). In vitro glomerular filtration rate analysis ((51)Cr-EDTA) and (99m)Tc-DMSA scintigraphy were performed before and after captopril administration in all patients. RESULTS: The mean baseline glomerular filtration rate was 48.6±21.8 ml/kg/1.73 m(2) in the group wuth renal artery stenosis, which was significantly lower than the GFR of 65.1±28.7 ml/kg/1.73m(2) in the group without renal artery stenosis (p=0.04). Captopril induced a significant reduction of the glomerular filtration rate in the group with renal artery stenosis (to 32.6±14.8 ml/ kg/1.73m(2), p=0.001) and an insignificant change in the group without RAS (to 62.2±23.6 ml/kg/1.73m(2), p=0.68). Scintigraphy with technetium-99m dimercapto-succinic acid (DMSA) did not show significant differences in differential renal function from baseline to post-captopril images in either group. CONCLUSIONS: Captopril induced a decrease in the GFR that could be quantitatively measured with (51)Cr-EDTA. The reduction is more pronounced in hypertensive patients with RAS.